Chronic pain, its management and psychological issues: A review - Jena, Monalisa; Mishra, Swati Mishra; Pradhan, Sarita; Jena, Swetalina; Mishra, Sudhansu Sekhar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Chronic pain is one of the most prevalent, disabling conditions both in clinical and psychological aspects and yet often remains inadequately treated due to cost reasons. Moreover, chronic pain commonly occurs in conjunction with depression, anxiety and somatoform disorders. Chronic and recurrent pain not associated with a disease is very common in childhood and adolescence, but there are very less studies and analysis has been done on chronic pain epidemiology and management. As pain is the important factor influencing quality of life and also the reason for which a person seek the advice of physician even require hospitalization that is why this systematic review highlights the different types of chronic pain, epidemiology, pathophysiology, and management of chronic pain along with psychological issues associated with it. Keywords: Pain, Psychological aspects, Epidemiology, Somatoform disord